2022
DOI: 10.3389/fpubh.2022.933333
|View full text |Cite
|
Sign up to set email alerts
|

Global research trends in MERS-CoV: A comprehensive bibliometric analysis from 2012 to 2021

Abstract: BackgroundThe Middle East respiratory syndrome coronavirus (MERS-CoV) was first reported in Saudi Arabia in 2012. So far, the cases of MERS-CoV have been reported in 27 countries. The virus causes severe health complications, resulting high mortality.AimThe current study aimed to evaluate the global research trends and key bibliometric indices in MERS-CoV research from 2012 to 2021.MethodsA retrospective bibliometric and visualized study was conducted. The Science Citation Index Expanded Edition of Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
3
6
0
Order By: Relevance
“…All the mentioned countries are economically developed. Similar to our findings, previous studies on scientific productivity have shown that economically developed countries are more productive regarding scientific studies ( 16 - 20 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All the mentioned countries are economically developed. Similar to our findings, previous studies on scientific productivity have shown that economically developed countries are more productive regarding scientific studies ( 16 - 20 ).…”
Section: Discussionsupporting
confidence: 92%
“…A comprehensive assessment of the state of hMPV research is necessary to guide future research goals, primarily through collaboration among numerous academic researchers in various fields. Our findings may have an impact on future theoretical research because a good indicator of production and advancement may be the number of publications over time ( 20 ).…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, a bibliometric analysis by Tauseef Ahmad showed that the United States and Saudi Arabia were the most active and funding countries. Their study also revealed that the Ministry of Health of Saudi Arabia was the most active institution, and Saudi Arabia was the country with the strongest cooperation ( 18 ). According to data from the Scopus database, another bibliometric analysis by Sa'ed H. Zyoud revealed a global increase in research on MERS-CoV from 2012 to 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, MERS-CoV like viruses have also been reported in different bats across the globe ( Anthony et al, 2017 ; Kim et al, 2016 ; Lau et al, 2018b ; Luo et al, 2018 ; Moreno et al, 2017 ; Yang et al, 2014 ). MERS-CoV is a zoonotic virus and the potential reservoirs are considered to be Bats and the intermediate hosts are dromedary camels (source of transmissions to human) ( Ahmad, 2022 ).…”
Section: Discussionmentioning
confidence: 99%